EFEKTIVITAS BAHAN ORGANIK DAN TINGGI GENANGAN TERHADAP PERUBAHAN Eh, pH, DAN STATUS Fe, P, Al TERLARUT PADA TANAH ULTISOL - muhammad Basir-cyio (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The aim of the research was to determine the value of redox potential (Eh), soil reaction (pH) and status of soluble soil Fe, P and Al as a result of organic matter addition under submerged condition in Ultisol Kulawi. It is expected that the research results could add more information; be used as consideration; and basis for effective paddy field management resulting in maximal production. The experimental research was conducted in March-June 2007. The sampled soil location was in Kulawi sub district, Donggala Regency, Central Sulawesi Province. Soil analysis was carried out in Soil Science Laboratory of Agricultural Faculty Tadulako University. The experiment used a Completely Randomized Block Design with factorial experiment. The first factor was various water depths: muddy (TG1), 10 cm (TG2), and 15 cm (TG3). The second factor was organic matter levels: 0 t ha-1 (BO1) and 15 t ha-1 (BO2). The various water depths and organic matter levels significantly increased the availability of phosphorous and significantly reduced the solubility of Fe and Al. Soil submergence with organic matter addition could improve soil fertility. The water depth of 10 cm with 20 t ha-1 organic matter was very effective in the paddy field management. With such condition soil pH increased close to neutral, available P improved, and Eh, soluble Fe and Al reducedKeywords : Organic matter, redox potential, and soil reaction